Efficiency of handmade attractants in fruit fly control (Bioagro, 2024)
Fruit flies (Diptera: Tephritidae) are considered the main pests of fruit crops worldwide, and using traps and attractants are useful tools for their effective monitoring and control. The study's main objective was to evaluate the capacity to capture fruit flies with non-commercially produced attractants and use the Lin and Binns method to evaluate their performance. Five food attractants were evaluated to capture the genera Anastrepha and Ceratitis. The study was carried out in five municipalities of Táchira State, Venezuela, during two semesters, using a completely randomized design with four replications. The experimental unit was represented by a JD EuGo 97 trap, baited with 300 mL of the respective attractant solution. The attractants did not perform equally in all environments, while no variation was observed in the level of trap capture between the two semesters studied. Anastrepha fraterculus was the only species collected at all altitudinal levels, suggesting an adequate capacity to adapt to different environments. The commercial product PedGo plus was the most effective attractant for fly trapping, and it may be an appropriate alternative for use by fruit growers in the control of this pest. Although it was the most efficient attractant in most of the environments studied, molasses + urea proved to be an alternative to replace PedGo plus and Nulure.